A method to improve quantitative radiotracing‐based analysis of the in vivo biodistribution of drug carriers - Nikša Roki; Melani Solomon; Lou Casta; Jessica Bowers; Robert C. Getts; Silvia Muro (Wiley, 2021)
Abstract Biodistribution studies are essential in drug carrier design and translation, and radiotracing provides a sensitive quantitation for this purpose. Yet, for biodegradable formulations, small amounts of free‐label signal may arise prior to or immediately after injection in animal models, causing potentially confounding biodistribution results. In this study, we refined a method to overcome this obstacle. First, we verified free signal generation in animal samples and then, mimicking it in a controllable setting, we injected mice intravenously with a radiolabeled drug carrier formulation (125I‐antibody/3DNA) containing a known amount of free radiolabel (125I), or free 125I alone as a control. Corrected biodistribution data were obtained by separating the free radiolabel from blood and organs postmortem, using trichloroacetic acid precipitation, and subtracting the confounding signal from each tissue measurement. Control free 125I‐radiolabel was detected at ≥85% accuracy in blood and tissues, validating the method. It biodistributed very heterogeneously among organs (0.6-39 %ID/g), indicating that any free 125I generated in the body or present in an injected formulation cannot be simply corrected to the free‐label fraction in the original preparation, but the free label must be empirically measured in each organ. Application of this method to the biodistribution of 125I‐antibody/3DNA, including formulations directed to endothelial target ICAM‐1, showed accurate classification of free 125I species in blood and tissues. In addition, this technique rendered data on the in vivo degradation of the traced agents over time. Thus, this is a valuable technique to obtain accurate measurements of biodistribution using 125I and possibly other radiotracers.